Bis(phosphonate)‐Building Blocks Modified with Fluorescent Dyes. Issue 5 (26th August 2013) - David, Tomáš; Kotek, Jan; Kubíček, Vojtěch; Tošner, Zdeněk; Hermann, Petr; Lukeš, Ivan
ABSTRACT Preparation of two benzylic bis(phosphonic acids) modified with primary amine or carboxylic acid groups on the benzene ring is described. These compounds were prepared and characterized in the form of both bis(phosphonate) tetraesters and corresponding free acids. The phosphonic acid esters are suitable for further derivation, mainly for conjugation through the amide bond. Mild conversion of the bis(phosphonate) esters to free acids using trimethylsilylbromide allowed to work with functional groups sensitive to conditions of acidic and/or alkaline hydrolysis. Three bis(phosphonate)‐containing fluorescent probes were prepared from the building blocks, utilizing amide and sulfamide bonds as spacers. Dyes containing the dansyl group, rhodamine B, and fluorescein were chosen due to their common availability and low cost. The prepared bis(phosphonate)‐building blocks and modified fluorescent probes were used for adsorption studies with hydroxyapatite, the commonly used model of bone tissue. Sorption ability of the prepared bis(phosphonate) compounds was similar to that of pamidronate.